ASSESSMENT OF THE PERCEIVED INCOME EARNED FROM POULTRY FARMING: IMPLICATIONS FOR POVERTY ALLEVIATION AMONG POULTRY FARMERS IN FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA - Onyemekihian, F.; Okwuokenye, G. F.; Jov, E. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study focused on the assessment of perceived income earned from poultry farming and the implications for poverty alleviation among poultry farmers in Federal Capital Territory, Abuja, Nigeria The study examine the socio-economic characteristics of the poultry farmers, evaluate the farm income realized from poultry farming, ascertain the farmers level of satisfaction on income earned from poultry production and ascertain the level to which poultry farming has helped to alleviate the poverty status of the farmers. Simple random technique was used to source for the 112 respondents that were used for the study. The data were sourced from primary and secondary sources. The primary data were analyzed with the use of descriptive and inferential statistics (Logistics regression and Binomial test). The results revealed that the average age, household size, farm size and farm experience was 43.30 years, 6 persons, 869 birds and 8.01 years respectively. Poultry farming was found to be profitable since they made an average income of N397,768.36. The farmers claimed that the income realized from poultry farming helped in alleviating their poverty level to a high extent. Socio-economic characteristics of the poultry farmers revealed that age, household size, farm experience, educational level and marital status have significant relationship with perceived income realized from poultry farming. The results also showed a significant difference between farmers that are satisfied and those not satisfied with the extent to which poultry farming has alleviated their poverty status. It was recommended that there is a need to coopt and focus on more young persons in the poultry farming business and that more females still need to be supported and encouraged into the poultry farming business so that the output and income realized will increase to meet more family needs and have more farmers poverty level alleviated.